Prochloraz residue levels in ginger submitted to Sportak 450 CE” postharvest treatment - Polese, Luciana; Jardim, Elaine Fátima Galatti; Navickiene, Sandro; Brito, Natilene Mesquita; Ribeiro, Maria Lucia (Eclética Química, 2006)
A preliminary study was conducted to determine the residue levels of prochloraz in ginger samples treated with Sportak 450 CE  (prochloraz as active ingredient) under laboratory conditions and cold-storage for 15 days at 10°C and 89% RH. Sampling was carried out at 10 and 15 days after Sportak 450 CE  dip treatment (450 and 900 μg mL -1 ). Pesticide residues were determined by GC- ECD. During the study, residue levels in ginger ranged between 3.6 and 10.6 mg Kg -1 for prochloraz.